Sustainable Human Resource Management Practices and Their Impact on Corporate Social Responsibility (CSR) and Employee Performance - Wandy Zulkarnaen; Tetty Sufianty Zafar (Global Research Collaboration, 2026)
This study aims to examine the effect of Sustainable Human Resource Management (HRM) practices on employee-perceived Corporate Social Responsibility (CSR) and employee performance, and to examine the mediating role of CSR in this relationship. The study used a sequential explanatory mixed-method design involving 52 qualitative informants from 6 organizations and 412 quantitative survey respondents. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Qualitative findings revealed seven main themes of sustainable HRM implementation, including the integration of sustainability in recruitment, training, performance management, and compensation. Quantitative results showed that sustainable HRM practices had a positive and significant effect on CSR (β = 0.623; p < 0.001) and employee performance (β = 0.418; p < 0.001). CSR also has a positive effect on employee performance (β = 0.349; p < 0.001) and partially mediates the relationship between sustainable HRM practices and employee performance (indirect effect β = 0.217; p < 0.001). The research model explains 38.8% of the variance in CSR and 45.2% of the variance in employee performance. This study extends the AMO (Ability-Motivation-Opportunity) Theory framework by identifying CSR as an additional pathway explaining how sustainable HRM practices affect individual performance. The practical implications emphasize the need for organizations to integrate sustainable HRM practices throughout the HRM cycle and effectively communicate CSR commitments to employees. This study provides theoretical and empirical contributions to the sustainable HRM and CSR literature from a micro perspective.